Antioxidant and antimicrobial activity of Rhizophora apiculata Blume and Rhizophora mucronata Lam - Tukimin, Tuhaila (2016)
Mangroves have many important roles from coastal protection, as a medicinal plant, conservation of biodiversity to industrial products; such as firewood, charcoal and pole piling. Rhizophora apiculata and Rhizophora mucronata are the most common species used in these industries. The aim of this study is to investigate the antioxidant and antimicrobial activity of these two species as a potential non-wood product. Three locations of mangrove type forest were selected, which included TPF (Timber production forest), VGF (Virgin forest) and SCF (Soil conservation forest). Parts of the plant such as fruit, leaf, root and twig were investigated for alcohol solubility, phenolic and flavonoid contents. Plant parts were extracted using ethanol and distilled water (80/20 by volume). The phenolic content was analyzed by Folin-Ciocalteau reagent using UV spectrophotometric technique while flavonoid content was measured by aluminium chloride colometric assay. The extracted samples were analyzed through a high performance liquid chromatography (HPLC) to identify the existing of phenolic compounds. Three antioxidant activities were investigated, i.e. ABTS [2,2-Azinobis (3-ethyl-benzothiazoline- 6-sulfonic acid)], DPPH (1,1-diphenly-2-picrylhydrazyl) assay and β-carotene bleaching assays. Antimicrobial activities were investigated by the use of disc diffusion method with Bacillus subtilis (B145), Staphylococcus aureus (S276), Salmonella cholerasuis (ATCC 10708), Escherichia coli (E266) and Candida albican (C244). Alcohol solubility is shown to be significantly different based on the part of the plant with the highest seen in descending order from fruit, leaf, twig and root. Based on the location, TPF showed the highest yield compared to SCF and VGF. R.mucronata showed the highest value from fruit (32.05%), while, R.apiculata presented the highest value at 35.06 % from leaves. Phenolic and flavonoid content were significantly different (p<0.05) on parts, location and also species. Twigs from R.mucronata at SCF presented the highest phenolic and flavonoid content with 41.01 mg GAE/g and 72.18 mg QE/g respectively. HPLC result showed that gallic acid was presented in all parts but not for cinnamic acid, caffiec acid and quercetine. Based on species, there were extra compounds present such as benzoic acid and vanillic acid in R.apiculata and salicylic acid in R.mucronata. All parts for the both species showed antioxidant activity by DPPH, ABTS and β-Carotene. However fruit and twig are the most prominent. DPPH radical scavenging discovered that R.apiculata and R.mucronata inhibit more capacity from fruit at 56.78% and 57.35% respectively. Through IC50 measurement on both species showed that the data from fruits have the lowest value at 101.09 μg/mL (R.apiculata) and 174.04 μg/mL (R. mucronata). ABTS capacity showed that R.mucronata inhibits the highest amount from fruits (70.91%) while R.apiculata were from twigs (57.60%). Twigs presented high amounts of β-Carotene for both species which were at 42.79% from R. apiculata and 54.62 % from R. mucronata. Antimicrobial activity presented that both species showed an inhibition area against bacterial strains of B. subtilis but were resistant to other strains except the twig part of R. mucronata. Fruits extrated from R.apiculata were inhibited more than others parts (10.00 mm), followed by twig (8.5 mm). Fruit and twig parts of R.mucronata showed a greater inhibition area than other parts which corresponded to 8.25 mm and 8.5 mm. Only the twig part of R.mucronata presented an inhibition zone 9.5 mm against Salmonella chlerasuis (ATTC 10708). From this study, these species presented antimicrobial activity within parts of plant, mainly from fruit and twig. This study revealed that twig and fruit parts presented high phenol and flavonoid content. These parts also exhibited a greater response to antioxidant and antimicrobial activity compared to other parts. R. mucronata is the outstanding species which is inhibited by a greater radical scavenging capacity than R. apiculata. This species also showed greater efficacy as an antimicrobial agent.